PENGARUH MEDIA PEMBELAJARAN KOTAK AJAIB TERHADAP HASIL BELAJAR MATEMATIKA MATERI PENJUMLAHAN BERSUSUN SISWA KELAS II SD N 35 PALEMBANG - Aulia Multi Anggraini; Muhammad Juliansyah Putra; Nora Surmilasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether there is an effect of the Magic Box learning media on the mathematics learning outcomes of second-grade students at SD N 35 Palembang in the subject of vertical addition. This research is a quantitative study that uses the quasi-experimental method. It was conducted at SD N 35 Palembang. Data collection techniques included tests and documentation. The study was carried out in class II A, which had 25 students as the experimental class, and class II B, which had 25 students as the control class. The instrument used was an essay question consisting of 10 items. The results of this study indicate that there is an effect of the Magic Box media on the learning outcomes of second-grade students at SD N 35 Palembang in addition, with a calculated t-value (3.418) > table t-value (0.1677) and a sig value (0.001) < (0.05). In accordance with the hypothesis testing, if the calculated t-value is greater than the table t-value, then the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted